CRIMINAL PRIVILEGE OF AN ATTORNEY AND DEFENCE LAWYER - V. Gracheva, Yulia; V. Malikov, Sergey; I. Chuchaev, Alexandr (Gênero & Direito, 2020)
The boundaries of the attorney-client privilege are the main issue of theory and practice that directly touches upon the content of the criminal privilege of an attorney and defense lawyer. In procedural law branches the prohibition of their examination is acknowledged axiomatic. The paper calls attention to the existing moral and legal problem associated with preserving the attorney-client privilege in all the circumstances without exception, including the cases when the disclosure thereof can be justified from the point of view of protecting the interests of a person, society and state. The authors admit the possibility of restriction thereof provided that the law reflects an exhaustive list of crimes, the information on preparation or commission of which will not fall under the content of the attorney-client privilege. As a result it is proposed to eliminate the existing gap in the criminal legislation of RF that can be used in the foreign law. The conclusions made by the authors are based on analyzing the judicial practice of the European Court of Human Rights (ECHR) for a period of 1980-2017; decisions and ruling of the Constitutional Court of RF made in 2001-2017; published judicial practice of the RF Supreme Court for 2003-2017; and results of the survey of 78 respondents (judges, prosecution office staff, attorneys and teachers of criminal law and proceedings).